INNOVATION ABILITY TEACHERS OF ISLAMIC EDUCATION IN IMPROVING THE QUALITY OF LEARNING IN SMP IT KHAIRUL IMAM MEDAN - Yulizawati, Saiful Akhyar Lubis, Edi Saputra (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This research aims to: 1) analyze the innovation ability of Islamic religious education teacher(PAI) in improving the quality of teachers in the SMP IT Khairul Imam Medan; 2) To analyse the effortsmade in enhancing the innovation and quality of Islamic education teachers (PAI) at SMP IT KhairulImam Medan; 3) to analyze the supporting factors and inhibitions increase the innovation of the teachersof Islamic Religious Education (PAI) in improving the quality of teachers at SMP IT Khairul Imam Medan.This research is a qualitative study with thePhenomenology method. Its data analysis techniques usinginteractive models of Miles and Huberman consist of data reduction, data presentation, and conclusion.The results showed that the innovation ability of Islamic religious education teacher (PAI) in improving thequality of learning at SMP IT Khairul Imam Medan has been innovating in the field of learning planning,implementation and evaluation. The efforts of Islamic religious education teacher (PAI) in improving thequality of learning at SMP IT Khairul Imam Medan is to participate in training, seminars, and learningdiscussions, following the MGMP conducted by the Education Office Approach to students to find methodsthat fit the situation of the students, as well as adapting props and learning media to support the learningdone in the classroom. As a contributing factor to the innovation ability of Islamic religious educationteacher (PAI) in improving the quality of learning at SMP IT Khairul Imam Medan is a cooperation betweenteachers, students, principals and foundations, availability of facilities and infrastructure That supportslearning and optimizing the proper use of media and learning methods. Meanwhile, the most significantfactor is the availability of time allocation of Islamic religious education (PAI) subjects which still lacks andsupport from the foundation that still needs to be improved.Keyword: Teachers, Learning and Inovation